Anal sphincter injury. Management and results of Parks sphincter repair. - Browning, G G (1984)
The surgical management of a consecutive series of 97 patients with complete division of the anal sphincter musculature is reported. The sphincter damage followed operative, traumatic, or obstetric injury and resulted in frank fecal incontinence or the urgent necessity of a defunctioning colostomy. All patients were treated by delayed sphincter repair using an overlapping technique; in 93 the repair was protected by a temporary defunctioning stoma. There were no deaths. The repair was completely successful in 65 (78%) and partially successful in 11 (13%) of the 83 patients assessed from 4 to 116 months after surgery. Complications occurred in 27 patients but did not usually affect the eventual clinical outcome. Provided there has been no major neurological damage to the sphincter complex, surgical reconstruction can be expected to restore continence in most patients.